Local coexistence and niche differences between the Lusitanian and Mediterranean pine voles (Microtus lusitanicus and M. duodecimcostatus) - Santos, Sara M. (2012)
In the present study, we analyzed the coexistence pattern of the Lusitanian pine vole (Microtus lusitanicus) and the Mediterranean pine vole (Microtus duodecimcostatus) in a potential area of sympatry in a Mediterranean landscape (Portugal). We also determined the relative contribution of local, landscape, and spatial factors explaining the diﬀerences in the distribution patterns of the two species in the region. Using a kriging interpolation method, we obtained a map of sympatric and allopatric areas of species occurrence. The estimated sympatry area corresponded to a north-west–southeast belt representing 11.3% of the study area. Habitat niche differences were assessed with binomial GLMs followed by a variance partitioning. At a local scale, higher altitude, higher cover of shrubs, lower clay content in the soil, and lower cover of tree canopy were the most important factors distinguishing M. lusitanicus presence sites from those with M. duodecimcostatus. At a larger scale, the presence of forest landscape units and the low abundance of ‘‘montado’’ units were the most inﬂuencing landscape factors in the identiﬁcation of M. lusitanicus occurrence sites when compared to M. duodecimcostatus. Our results suggested that local coexistence of M. lusitanicus and M. duodecimcostatus in the ﬁeld is a rare event. The differences in distribution patterns of the two pine vole species were mostly explained by ﬁne-scale environmental factors and by shared spatial effects.